Profitabilitas, Leverage, serta Ukuran Perusahaan: Kunci Kebijakan Dividen di Perusahaan LQ 45 Bursa Efek Indonesia - Hasanah, Inna Nur; Sari, Dian Anita (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
ABSTRACT The purpose of this study is to examine how profitability, leverage, and company size affect dividend policy in LQ 45 firms that are listed on the BEI. The population that is the focus of the research this is an LQ 45 company listed on BEI during period 2019-2023. In the research, sample used consisted of 21 company LQ 45. The sampling method applied is purposive sampling. Meanwhile, for data analysis, regression techniques were used multiple linear. The study's findings indicate that, for LQ 45 companies listed on the BEI, size has a major positive impact on dividend policy, profitability has a negligible negative impact, and leverage has a negligible negative impact. Adjusted R Value 2 which obtained at 0.142 indicating that there is 14.2% variation in dividend policy on LQ 45 companies listed on the BEI can be explained by the three independent variables, namely profitability, leverage and size company. Meanwhile, the remaining 85.8% is explained by other variables which were not analyzed in this study.